A new approach for identifying phases of the breaststroke wave kick and calculation of feet slip using 3D automatic motion tracking - Olstad, B. H.; Zinner, C.; Haakonsen, D.; Cabri, J.; Kjendlie, P. L. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
This study proposes a new method for identifying the different phases of the leg kick in the modern breaststroke technique. Previous analysis models assume that all breaststroke kicks finish with feet actively coming together during the insweep followed by a 'flat glide' and active knee bend to start the recovery. Using the previous models for the swimmers tested the phases could not be accurately separated due to the different wave amplitudes in their technique influencing their insweep and knee bend timing during recovery. Four phases of the breaststroke kick were therefore identified using 3D automatic motion tracking: 1) propulsion, from the smallest knee angle during recovery of the legs until the first peak in knee angle during propulsion, 2) insweep/wave motion/glide, from end of phase 1 until second peak in knee angle, 3) first part of the recovery, from end of phase 2 until 90 degree knee angle and 4) second part of recovery, from end of phase 3 until legs reach position 1. The method uses distinct positions of the 3D markers, their trajectory and peak angles to give a better understanding of the phases in the modern breaststroke technique as well as accounting for different styles of breaststroke technique.